Involvement of growth differentiation factor-15/macrophage inhibitory cytokine-1 (GDF-15/MIC-1) in oxLDL-induced apoptosis of human macrophages in vitro and in arteriosclerotic lesions - Schlittenhardt, Daniel; Schober, Andreas; Strelau, Jens; Bonaterra, Gabriel; Schmiedt, Walther; Unsicker, Klaus; Metz, Jürgen; Kinscherf, Ralf (Cell & tissue research, 2004)
Growth differentiation factor-15/macrophage inhibitory cytokine-1 (GDF-15/MIC-1) is a new member of the transforming growth factor beta (TGF-β) superfamily, which has most recently been found in activated macrophages (MΦ). We have now investigated GDF-15/MIC-1 in human MΦ after exposure to oxidized low-density lipoproteins (oxLDL) related mediators in vitro and in arteriosclerotic carotid arteries. Using RT-PCR and Western blotting a pronounced induction of GDF-15/MIC-1 expression by oxLDL, C6-ceramide, tumor necrosis factor (TNFα) and hydrogen peroxide (H2O2) was found in cultured human MΦ. In 11 human arteriosclerotic carotid arteries, immunohistochemical analyses supported by computer-assisted morphometry and regression analyses demonstrated a significant colocalization of GDF-15/MIC-1 immunoreactivity (IR) with oxLDL IR and manganese superoxide dismutase (MnSOD) IR in CD68 immunoreactive (ir) MΦ, which were also expressing AIF-IR (apoptosis-inducing factor), caspase-3-IR (CPP32), PARP-IR, c-Jun/AP-1-IR and p53-IR. Our data suggest that GDF-15/MIC-1 is inducible in human MΦ by oxLDL and its mediators in vitro and is supposed to contribute to oxidative stress dependent consequences in arteriosclerotic plaques, e.g. modulating apoptosis and inflammatory processes in activated MΦ.